17-α hydroxyprogesterone caproate for the prevention of preterm birth. (January 2012) - Gupta, Simi; Roman, Ashley S
17 α hydroxyprogesterone caproate is a synthetic form of the natural progestin 17-α hydroxyprogesterone that is US FDA approved for the prevention of recurrent spontaneous preterm birth in women with a history of a prior singleton preterm birth. For women with a history of a prior spontaneous preterm birth between 20 weeks and 36 weeks and 6 days of gestation, the use of 17-α hydroxyprogesterone caproate has been shown to reduce the risk of recurrent preterm birth by more than 30%. This medication is the only drug currently FDA approved for the prevention of preterm birth, and it is the first drug the FDA has approved for use exclusively during pregnancy in approximately 15 years.